Pengembangan Sistem Informasi Akuntansi Berbasis Desktop Dengan Metode Stradis - Raissa Amanda Putri; Laylan Syafina (ALGORITMA : JURNAL ILMU KOMPUTER DAN INFORMATIKA, 2018)
With the development of information technology that exists today we can do data processing easily, canproduce an information that we need with accurate and effective time, and with the costs we spend moreefficiently. Likewise in the management of financial data, information technology is an important thingfor companies in managing financial data because it is expected to be able to assist the finance oraccounting department in producing more accurate financial reports, and to make effective time in itspreparation.